Perancangan Pakaian Formal Convertible Untuk Brand Prim & Proper Yang Ditujukan Kepada Wanita Karir - Melisa Wibisono; Rahayu Handayani (Jurnal Vicidi, 2017)
"Designing Convertible Formal Clothes For Prime & Proper Brand Made for Indonesian Career Women" is about the production process of women's clothing with the concept of a convertible in helping the activities and lifestyle of Indonesian career women. This is related to the needs of career women in this dense era of globalization that requires them to maximize the effectiveness of time as well as show a professional appearance by adjusting the activities and events that take place. With the concept of a fashion convertible, it will provide the ease and effectiveness of time without reducing the aesthetics of everyday clothes which still comfortable and easy to use. Keyword: Career, Clothing, Convertible, Fashion, Women